2006
DOI: 10.1213/01.ane.0000189561.44016.99
|View full text |Cite|
|
Sign up to set email alerts
|

Desflurane Anesthesia After Sevoflurane Inhaled Induction Reduces Severity of Emergence Agitation in Children Undergoing Minor Ear-Nose-Throat Surgery Compared with Sevoflurane Induction and Maintenance: Retracted

Abstract: Emergence agitation may occur after general anesthesia with volatile anesthetics in children. We designed this study to examine the emergence behavior of children undergoing ear-nose-throat surgery after sevoflurane induction and desflurane maintenance versus both sevoflurane induction and maintenance using a recently published Pediatric Anesthesia Emergence Delirium (PAED) scale. In 38 premedicated children aged 12 mo to 7 yr mask induction with sevoflurane was performed and they were randomly assigned to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 22 publications
2
23
0
3
Order By: Relevance
“…The reliability and validity of the PAED scale have been confirmed by several studies, and the average PAED score when sevoflurane is used is 7.2 ± 4.5 [11] or 12 (range, 2-20) [22]. In this study, the PAED score on arrival at the PACU was 7.3 for the FICB group and 10.4 for the control group.…”
Section: Discussionsupporting
confidence: 73%
“…The reliability and validity of the PAED scale have been confirmed by several studies, and the average PAED score when sevoflurane is used is 7.2 ± 4.5 [11] or 12 (range, 2-20) [22]. In this study, the PAED score on arrival at the PACU was 7.3 for the FICB group and 10.4 for the control group.…”
Section: Discussionsupporting
confidence: 73%
“…Sale et al [10], concluded that infants woke up faster from general anaesthesia when maintained with desflurane as compared to sevoflurane, but there was no difference in postoperative respiratory events between the groups. Mayer et al [11], concluded that the use of desflurane for maintenance of anesthesia after sevoflurane induction in children is associated with less severe emergence agitation and faster emergence. Macario et al [12], concluded that patients receiving desflurane recovered one to two minutes earlier in the operating room than patients receiving sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) Mayer ve ark. 'nın (19) sevofluran indüksiyonu sonrasında anestezi idamesinde desfluran ve sevofluranı karşılaştırdığı bir çalışmada da, desfluran alan grupta derlenmenin daha hızlı olduğu, postoperatif ajitasyonunun ise sevofluran grubunda anlamlı olarak yüksek olduğu gösterilmiştir.…”
Section: Gereç Ve Yöntemunclassified